Efeito de dosagens crescentes de fosfato de rocha sobre nodulação, infecção micorrizica vesículo-arbuscular e crescimento de mudas de algaroba (Prosopis juliflora (SW.) DC.) - Freire, Vânia Felipe (1986)
Two experiments were conducted under greenhouse conditions to evaluate the effect of increasing rock phosphate levels on nodulation, VA mycorrhizal infection and growth of algarroba (Prosopis juliflora (SW.) DC.) [...]